Improvement of memory deficits via acetylcholinesterase inhibitory activity of Nepeta nuda ssp. nuda essential oil in rats - Akbaba, Emel; Bagci, Eyup; Hritcu, Lucian; Maniu, Calin (Elsevier, 2021)
Nepeta L. (Lamiaceae) species are belonging to aromatic and medicinal plants. Many biological activities of Nepeta species have been reported. In this study, memory-enhancing activities of Nepeta nuda ssp. nuda essential oil was aimed to be evaluated in laboratory rats treated with scopolamine. GC-MS/GC-FID system was used to identify oil composition. Memory performances of the rats were tested using Y-maze and radial-arm maze. Acetylcholinesterase enzyme activity and molecular docking analysis were also performed in this study. In total, 44 different compounds were identified in Nepeta nuda ssp. nuda essential oil. Trans-cis nepetalactone was showed to be the most abundant constituent in the oil. In the Y-maze test, the oil improved the performances of the animals on spontaneous alternation. Besides, in the radial-arm maze test, the oil improved working and reference memory significantly impaired in the rats subjected to scopolamine. The oil also showed acetylcholinesterase inhibitory activity in vitro. The molecular docking method, in the meantime, revealed that some of the compounds in the oil could interact with the acetylcholinesterase enzyme, theoretically. Nepeta nuda ssp. nuda essential oil improved spatial memory of scopolamine-induced rats. Neuroprotective effects of the oil are probably related to the anti-cholinesterase activity of the oil. Therefore, Nepeta nuda ssp. nuda essential oil could be used as a complementary therapy to improve memory in Alzheimer's and related diseases.
Keywords: Essential oil; memory; Nepeta nuda; scopolamine; Y-maze